Notes on land occupations and agrarian unionism, 1945-1964 - Flores Galindo, Alberto (1978)
As of 1945, in the central highlands, various communities begin to manage their official recognition, cumbersome legal proceedings between the community members and the landowners are initiated or resumed, some of which, as in the case of Huasicancha and the Laive hacienda, date back to to the 17th century, at the same time that within the haciendas the relations of personal dependency enter into a definitive crisis when the settlers begin to form their first unions. The process was interrupted by the military coup led by Manuel Odría and by the dictatorial obstacles that he imposed on popular organizations and trade unionism.